Effect of strain rate on tensile fracture behavior of notched polyamide 12 processed by selective laser sintering. (October 2022) - Gómez-del Río, T.; Crespo, M.; López, R.; Rodríguez, J.
Highlights: TCD was applied at high loading rates to failure of notched additive manufactured PA12. A probabilistic fracture toughness at different loading rates has been determined. Fracture toughness at different orientations was measured in additive manufactured PA12. An assessment of the Hopkinson bar experiments with notched samples is performed. Abstract: In this work, the applicability of the Theory of Critical Distances to the study of failure at high-loadings rates of polyamide 12 notched specimens additively manufactured by selective laser sintering, is evaluated. An experimental and numerical study has been carried out and values of modulus of elasticity, tensile strength and fracture toughness have been obtained. under static and dynamic conditions. The effect of orientation has also been analyzed, testing samples parallel and perpendicular to the layers of material deposited.